VASA (DDX4) is a Putative Marker for Spermatogonia, Spermatocytes and Round Spermatids in Stallions. Issue 6 (20th October 2015) - Kim, JY; Jung, HJ; Yoon, MJ
Contents: Expression of the protein DDX4/MVH, or VASA, has been reported in germ cells of several species. The main objectives of this study were to (i) investigate VASA expression patterns in testicular cells of stallions at two different reproductive stages (pre‐pubertal and post‐pubertal) and (ii) evaluate the use of VASA antibody as a molecular marker for single germ cells from stallions. Testicular tissues were obtained from stallions and categorized as pre‐pubertal and post‐pubertal based on the formation of lumen and status of spermatogenesis on the cross section of seminiferous tubules. The results of Western blot showed a VASA protein band located at 76 kDa, indicating that the rabbit antibody has a cross‐reactivity with horse testicular tissues. The result of immunolabelling showed that VASA was expressed in the cytoplasm of spermatogonia at both reproductive stages and in spermatocytes and round spermatids at the post‐pubertal stage. GATA4‐positive Sertoli cells and Leydig cells located in the interstitial space were not immunolabelled with VASA. These results suggest that VASA can be utilized as a molecular marker for germ cells of stallions at pre‐pubertal and post‐pubertal stages. Interestingly, immunolabelling intensity was significantly higher in pachytene spermatocytes compared to spermatogonia and round spermatid. VASA antibody was also effective for staining of single germ cell preparations. In conclusion, VASA protein expression can be used as a marker for identification of spermatogonia, spermatocytes and round spermatids in testicular tissues of stallions.